Nicotinic acetylcholine receptor α7 subunits with a C2 cytoplasmic loop yellow fluorescent protein insertion form functional receptors - Murray Teresa A; Liu Qiang; Whiteaker Paul; Wu Jie; Lukas Ronald J (Acta Pharmacologica Sinica; Vol 30, No 6 (June 2009): Acta Pharmacologica Sinica(Special Feature:Nicotinic Receptors and Nicotine Addiction）, 2016)
Aim: Several nicotinic acetylcholine receptor (nAChR) subunits have been engineered as fluorescent protein (FP) fusions and exploited to illuminate features of nAChRs. The aim of this work was to create a FP fusion in the nAChR α7 subunit without compromising formation of functional receptors. Methods: A gene construct was generated to introduce yellow fluorescent protein (YFP), in frame, into the otherwise unaltered, large, second cytoplamsic loop between the third and fourth transmembrane domains of the mouse nAChR α7 subunit (α7Y). SH-EP1 cells were transfected with mouse nAChR wild type α7 subunits (α7) or with α7Y subunits, alone or with the chaperone protein, hRIC-3. Receptor function was assessed using whole-cell current recording. Receptor expression was measured with 125I-labeled α-bungarotoxin (I-Bgt) binding, laser scanning confocal microscopy, and total internal reflectance fluorescence (TIRF) microscopy. Results: Whole-cell currents revealed that α7Y nAChRs and α7 nAChRs were functional with comparable EC50 values for the α7 nAChR-selective agonist, choline, and IC50 values for the α7 nAChR-selective antagonist, methyllycaconitine. I-Bgt binding was detected only after co-expression with hRIC-3. Confocal microscopy revealed that α7Y had primarily intracellular rather than surface expression. TIRF microscopy confirmed that little α7Y localized to the plasma membrane, typical of α7 nAChRs. Conclusion: nAChRs composed as homooligomers of α7Y subunits containing cytoplasmic loop YFP have functional, ligand binding, and trafficking characteristics similar to those of α7 nAChRs. α7Y nAChRs may be used to elucidate properties of α7 nAChRs and to identify and develop novel probes for these receptors, perhaps in high-throughput fashion.